Effect of ethanolic extract of Justicia secunda (blood root) leaves on reproductive organs and hormones in female Wistar rats - Okpara, Elile P.; Victor, Progress D.; Reuben, Edith; Ajie, Pearl C.; Fiala, Lolia T. (International Journal of Research in Medical Sciences, 2022)
Background: Several environmental chemicals are suspected to be responsible for adverse health effects on the reproductive system. Poisonous plants grow in most communities found on range lands and pastures. One major effect on consumption of these plants is on reproduction which includes birth defect, abortion and interference with Oogenesis, spermatogenesis, libido and estrous cycle. Justicia secunda (blood root) as the name implies is known for its anti-anemic properties. Methods: Animals were grouped into 6 groups with 6 rats in each group. They were housed in metal cages at room temperature and had access to commercial standard rodent pellets and clean water. Group 1 (control 0.00 mg/kg.) was given distilled water, groups 2-6 were given 99% ethanolic extract of Justicia secunda leaves orally at dose levels of 300, 400, 400, 450 and 450 mg/day, respectively for 42 days. Results: The result of this study indicates that ethanolic extract of Justicia secunda (blood root) was able to increase the level of FSH significantly at medium dose group. Significant increase in oestrogen level observed in this study. Conclusions: ethanolic extract of Justicia secunda (blood root) leaves is likely to cause an increase in the secreting ability of cells of the anterior pituitary gland producing FSH or cells of the hypothalamus producing gonadotrophin releasing hormones. The plant is likely to contain steroids.